Development of PjBL Module to Improve Students’ Collaboration in Informatics - Mustari S. Lamada; Hasrul Bakri; A. Sriwana Armi; Aulyah Zakilah Ifani (Journal of Computers, Informatics, and Vocational Education, 2025)
This research focuses on the development of a learning module for the Informatics subject, grounded in the Project-Based Learning (PjBL) approach, aimed at enhancing the collaboration skills of students at SMAN 4 Sinjai. The PjBL model is deemed appropriate as it promotes teamwork, collaborative problem-solving, and student involvement in real-world, meaningful projects. The study adopts the Research and Development (R&D) methodology using the 4D model, which includes the phases of Define, Design, Develop, and Disseminate. The participants of the study were eleventh-grade students. Research tools utilized comprised expert validation forms, student feedback questionnaires, and learning outcome assessment instruments. Findings indicated that the module achieved a high validity score from content experts (94.6%) and was considered valid by media experts (84.2%). Student feedback placed the module in the "very practical" category, with an average score of 90%. Furthermore, its effectiveness was reflected in improved student achievement, with an average post-test score of 88.18%. Consequently, the PjBL-based module is considered suitable for use as an instructional resource that effectively supports the development of students' collaboration skills in senior high school Informatics education.